Alleviation of Gut Inflammation by Cdx2/Pxr Pathway in a Mouse Model of Chemical Colitis - Dou, Wei (Public Library of Science, 2012)
Pregnane X Receptor (PXR), a master regulator of drug metabolism and inflammation, is abundantly expressed in the gastrointestinal tract. Baicalein and its O-glucuronide baicalin are potent anti-inflammatory and anti-cancer herbal flavonoids that undergo a complex cycle of interconversion in the liver and gut. We sought to investigate the role these flavonoids play in inhibiting gut inflammation by an axis involving PXR and other potential factors. The consequences of PXR regulation and activation by the herbal flavonoids, baicalein and baicalin were evaluated in vitro in human colon carcinoma cells and in vivo using wild-type, Pxr-null, and humanized (hPXR) PXR mice. Baicalein, but not its glucuronidated metabolite baicalin, activates PXR in a Cdx2-dependent manner in vitro, in human colon carcinoma LS174T cells, and in the murine colon in vivo. While both flavonoids abrogate dextran sodium sulfate (DSS)-mediated colon inflammation in vivo, oral delivery of a potent bacterial β-glucuronidase inhibitor eliminates baicalin’s effect on gastrointestinal inflammation by preventing the microbial conversion of baicalin to baicalien. Finally, reduction of gastrointestinal inflammation requires the binding of Cdx2 to a specific proximal site on the PXR promoter. Pharmacological targeting of intestinal PXR using natural metabolically labile ligands could serve as effective and potent therapeutics for gut inflammation that avert systemic drug interactions.